Calidad De Vida E Inclusión Social En Centros De Desarrollo Infantil Del Ministerio De Desarrollo Social Del Gobierno De La Ciudad De Buenos Aires - Kerman, Bernardo (European Scientific Journal, ESJ, 2016)
The study of the quality of life of a population is essential to understand the psychosocial factors involved and to develop specific intervention policies. According to this idea, an exploratory and descriptive study on the perception of adults attending Child Development Centers about their quality of life and their own families social inclusion is performed. In order to do this we work on a sample of 600 people on three scales that allow evaluation: 1. Quality of life. Well-being Index, WBI International Well being group. (Translation by Tonon & Aguirre (Argentina, 2009) 2. Resilience: Resilience Scale of Wagnild & Young 3. Well being: Well being Scale (Keyes). The scales denote subjective perceptions that participants have about their situation in the cultural context and the value system in which they live, in relation to their achievements, expectations and interests. The main goal is to determine the perception of families about their quality of life and social inclusion on the basis of the mentioned scales and indicators.